Hubungan Pengetahuan Agama Islam terhadap Pemahaman Nilai-Nilai Pancasila Siswa di SMP Royal Wells Middle Schools - Muhammad Resky; M. Syakhil Afkar R; Catur Febri Nusahid; Lusiana Lusiana; Yayat Suharyat (Lembaga Pengembangan Kinerja Dosen, 2022)
The religious, cultural, and ethnic diversity of Indonesia is well-known. Differences in understanding, nationality, and religion are frequently the primary causes of existing difficulties, to name just a few. This study sought to ascertain the relationship between eighth-grade students at SMP Royal Wells Middle School's knowledge and understanding of Islam and the Pancasila ideals. This study used a quantitative research method using a correlational approach. Understanding of Pancasila values is variable Y in this study, while Islamic religious knowledge is variable X. The population of this study consisted of 20 students, and the method of data collection used in it was distributing a questionnaire to eighth-graders at Royal Wells Middle School. The findings revealed a moderate link between Pancasila ideals and knowledge and understanding of Islam. Students can thus use the information on religious values and Pancasila both in the context of the classroom and in the community.